2019
DOI: 10.21037/gs.2018.10.01
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid surgery YouTube videos: estimating quality by surgeon characteristics and view rate

Abstract: Background: With readily available material online we aimed: (I) to estimate the volume of thyroid surgery-related video content readily available to the surgical trainee; (II) to stratify the sources of thyroid surgery-related video content by source (patient, institution, surgeon, or other) and (III) to estimate the quality of the surgeon source by related scholarly output.Methods: A search of YouTube, a widely used source of open-access video content, was undertaken using "thyroidectomy" as the search term.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…Several studies in the literature have evaluated medical YouTube videos [7][8][9]15,16,[23][24][25] ; however, only a few studies have evaluated orthodontic YouTube videos. 10,22,26 One YouTube analysis by Livas et al 26 was based on video content and metric evaluations of patients' Invisalign experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature have evaluated medical YouTube videos [7][8][9]15,16,[23][24][25] ; however, only a few studies have evaluated orthodontic YouTube videos. 10,22,26 One YouTube analysis by Livas et al 26 was based on video content and metric evaluations of patients' Invisalign experiences.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the majority of videos were posted by surgeons without a publication history in thyroid surgery. 9 The novel coronavirus 2019 (COVID-19) pandemic has brought unprecedented challenges to the healthcare community. While providing clinical care and ensuring public health are key priorities, it is important to consider the impact of COVID-19 on surgical education.…”
Section: Introductionmentioning
confidence: 99%
“…), selected initial propositions based on personal experience, video guidelines of major journals, and a literature review. 3,5,10,[12][13][14][15][17][18][19][20][21][22][23] A Delphi questionnaire was created, and the propositions were reviewed online by the entire consensus committee in three rounds. Blinded feedback was shared among respondents between each round, and the respondents were able to suggest new propositions at the end of round 1.…”
Section: Methodsmentioning
confidence: 99%
“…4,[10][11][12] Educational surgery videos that are available online are too often of insufficient quality and are rarely peer reviewed. 5,11,[13][14][15][16] Guidelines are available for other specialties, such as general surgery, to help improve the quality of the videos, but none are available in otorhinolaryngology. 17,18 Our specialty is well suited to the creation of surgical videos, particularly when using endoscopes or microscopes in otology, rhinology, or laryngology, as first-person surgical films are readily available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation